Leveraging Delphi Technique to Develop Breastfeeding Support Modules in East Java, Indonesia - Kowara, Mellysa; Lubis, Dinar Saurmauli; Crosita, Yessi; Octaviana, Betty; Kurnianingsih, I Desak Ketut Dewi Satiawati; Januraga, Pande Putu (Jurnal Kesehatan Masyarakat, 2024)
Improving knowledge and skills are crucial factors in increasing the commitment of health facility staff to support exclusive breastfeeding. This study presents the steps to formulate the modules using Delphi technique and implemented those modules in the training. This study used a mix-methods method consisting of four stages, namely literature review, qualitative study, module validity and module implementation. The modules were validated by 14 lactation experts to assess reliability, feasibility, and linguistics.  The study was conducted from 2020-2021 in 5 regions in East Java Province. A pre-post-test measurement with 493 health works and non-health workers was conducted to assess the effectiveness of the modules. The first round of Delphi showed agreement proportion between 80-100% on the three aspects. In the second round of Delphi, the strong consensus stated that the modules can be implemented in training was achieved with percentage of feasibility (79.4%), reliability (44.4%) and linguistics (44.4%). The results of the training using the modules showed a significant improvement in knowledge between 6-26 points in 5 areas (p-value0.000). In conclusion, three modules have been developed and validated successfully. The modules were effectively used to improve the breastfeeding knowledge and practice among health and non-health workers.